ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA PEGAWAI PADA PT BETAMI - Khairi, Mujibur (AKSIOMA : Jurnal Manajemen, 2022)
This research is used to determine whether leadership style and work environment affect employee job satisfaction. The research implementation is located at PT Betami with a sample of 31 respondents. This study uses a Likert scale. Data analysis used multiple linear regression. The results of the study concluded that the results of the t test of leadership style and work environment had no significant positive effect on employee job satisfaction, but through the F test, both had a significant positive effect.